Mass spectrometry techniques for studying the ubiquitin system. (22nd September 2017) - Heap, Rachel E.; Gant, Megan S.; Lamoliatte, Frederic; Peltier, Julien; Trost, Matthias
Abstract : Post-translational control of proteins through covalent attachment of ubiquitin plays important roles in all eukaryotic cell functions. The ubiquitin system in humans consists of 2 E1, 35 E2 and >600 E3 ubiquitin ligases as well as hundreds of deubiquitylases, which reverse ubiquitin attachment. Moreover, there are hundreds of proteins with ubiquitin-binding domains that bind one of the eight possible polyubiquitin chains. Dysfunction of the ubiquitin system is associated with many diseases such as cancer, autoimmunity and neurodegeneration, demonstrating the importance of ubiquitylation. Therefore, enzymes of the ubiquitin system are considered highly attractive drug targets. In recent years, mass spectrometry (MS)-based techniques have become increasingly important in the deciphering of the ubiquitin system. This short review addresses the state-of-the-art MS techniques for the identification of ubiquitylated proteins and their ubiquitylation sites. We also discuss the identification and quantitation of ubiquitin chain topologies and highlight how the activity of enzymes in the ubiquitin pathway can be measured. Finally, we present current MS tools that can be used for drug discovery in the ubiquitin space.